IMPLEMENTASI KEPERAWATAN PADA LANSIA GASTRITIS DENGAN MASALAH UTAMA NYERI AKUT DI IRYOU HOUJIN AIWAKAI (IKEDA-EN) JEPANG - AMBARWATI, RANGGAH REGINA CITRA; Sekar Siwi, Adiratna; Khasanah, Suci (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2025)
Gastritis is inflammation of the gastric mucosa caused by various factors, including Helicobacter pylori infection, irregular eating patterns, stress, and the consumption of alcohol and certain medications. Gastritis can be acute or chronic, with symptoms such as epigastric pain, nausea, vomiting, and bleeding. Treatment for gastritis involves conservative and pharmacological therapy, with a focus on pain management. This study aims to assess nursing care for gastritis patients with the primary issue of acute pain through the implementation of deep breathing relaxation techniques at Iryou Houjin Aiwakai Clinic, Japan. The research used a case study method with data collection through observation, interviews, physical examinations, and document studies. The results show that nursing interventions using deep breathing relaxation techniques reduced the pain scale from 5 to 3 within 3x24 hours. Additionally, the administration of medications such as Polaprezinc, Tsumura Rikkunshito, Polikarbophil C, and Lansoprazole was effective in alleviating gastritis symptoms. Nursing evaluation was carried out by analyzing the patient's response to the interventions, which showed a reduction in symptoms. This study concludes that a combination of pharmacological and non-pharmacological therapies can accelerate the healing process in gastritis patients.